PEMANFAATAN TEKNOLOGI ARTIFICIAL INTELLIGENCE PADA PLATFORM CANVA DALAM TRANSFORMASI MEDIA PEMBELAJARAN BAGI GURU SEKOLAH DASAR - Rusyda Maulida; Tita Puspitasari (JISPE Journal of Islamic Primary Education, 2025)
The rapid development of Artificial Intelligence (AI) technology has created new opportunities for the development of instructional media in primary education. However, its utilization by teachers still faces several challenges, particularly related to design skills, time efficiency, and the suitability of learning media to students’ characteristics. This study aims to examine the use of AI features on the Canva platform in developing instructional media at SD Daarul Qur’an Internasional, focusing on ease of use, teachers’ work efficiency, transformation of work patterns, and technical and pedagogical challenges encountered. This research employed a descriptive qualitative approach, with data collected through classroom observations, in-depth interviews with all teachers, and documentation analysis of instructional media products. Data were analyzed interactively using the Miles and Huberman model and validated through triangulation and member checking. The findings indicate that Canva AI is easy to use for teachers with diverse levels of digital competence, significantly improves time efficiency, and facilitates a transformation in teachers’ roles from manual content creators to more strategic and creative instructional designers. The instructional media produced are more varied, visual, and adaptive to the characteristics of primary school students. The main challenges identified include internet connectivity stability and the need to adjust AI-generated language to suit students’ cognitive development levels. This study concludes that Canva AI has strong potential to serve as a catalyst for pedagogical transformation in primary education when supported by adequate infrastructure and continuous professional development for teachers.